2022
DOI: 10.3390/coatings12030309
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Influence of Particle Shape on the Chemical Resistance of Epoxy Coating and Use of Waste Glass as the Filler

Abstract: The use of suitable secondary raw materials as fillers in progressive, protective agents primarily intended for horizontal concrete construction is very effective not only from the ecological but also from the economic point of view. The impact of using various types of waste glass as fillers on the mechanical parameters of epoxy coatings was experimentally verified. Assessing the dependency of the coating’s chemical resistance on the shape of the used filler’s particles was the main aim of the performed resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The amount of polymer binder used was determined according to the filling. The filling with secondary raw material was chosen based on previous research, where 25 wt.% filling was used [32], to test the waste parameters and viscosity of the polymer resin. The proposed formulations were tested in fresh and polymerised states.…”
Section: Fillersmentioning
confidence: 99%
“…The amount of polymer binder used was determined according to the filling. The filling with secondary raw material was chosen based on previous research, where 25 wt.% filling was used [32], to test the waste parameters and viscosity of the polymer resin. The proposed formulations were tested in fresh and polymerised states.…”
Section: Fillersmentioning
confidence: 99%
“…The elastomers mass of nitrile-butadiene rubber NBR, epoxy elastomers and polyurethane elastomers decreased substantially and complete degradation occurred after immersed in chemical solutions with 1 month. [50][51] Therefore, compared with (NBR), epoxy elastomers and polyurethane elastomers, PU-15UPy exhibited excellent chemical resistance performance.…”
Section: Chemical Resistance Performance Of Pu-15upymentioning
confidence: 99%
“…It was found that the addition of glass powder in a proportion of 19.4% to the epoxy resin is the most beneficial and increases the peel strength of the mortar. Epoxy coatings modified with glass waste were also obtained by Jana Hodná et al [20]. Thanks to the use of waste glass as filler, the tensile strength and hardness were improved, and its addition did not negatively affect chemical resistance or adhesion to the substrate.…”
Section: Introductionmentioning
confidence: 98%